Penyimpangan Perilaku Sosial Remaja di Kota Samarinda - Supratman, Nanang (SYAMIL, 2016)
Background of this research was condition of adolescents who experience behavioral disorder, repetitive and sedentary behavioral patterns, which it violated social norms and rules of their age or deviated from the truth. This behavioral disorder was backgrounded by factors which supported each other. The primary factors were internalization process of religion and culture, and fulfillment of developmental tasks. The other factors were systems of value, attitude, and belief, that guided behavior and represented social persfektive or moral conviction which was used as a last rational basis of action. Objective of this research were to explain the concept of value had by the adolescents who experience social behavioral irregularities and to show clearly the developmental tasks had by them, with Developmental Psychology expert theory. Qualitative research used was interdisciplinary approach. They were phenomenology, psychology, and sociology. Data collection techniques were interview and observation. Data analyzing were inductive and sustainable, that accorded to data collection framework, data reducting, data presenting, and conclusions (verification). The Validity of data used credibility testing which were extension of observation, enhancement of endurance, and triangulation. Then, the research used confirmability testing. Â The research were pointed out two (2) findings. One was the concept of value had, believed, and followed by the adolescents who experince social behavioral irregularities, was guided by some primary values -responsibility, aid, honesty, ambition, and rigth perception- and by some primary last ideals -having happiness, family safety, comfortable life, and value of true friendship- for having a life full of passion. Another was behavioral disorder that happened because of two (2) detentions. Detention in having the developmental tasks âunmature relation of friends around, failed reaching of masculinity and femininity socially, detenty accepting of body physically, and detenty reaching of emmotional independence of parents in some teenagers while some ones had not right independenceâ Â hence, inflicting less harmonious relation of adolescents among their parents and socials around. Detention in self preparing the family life âcarrer of economic, set of value and ethic system in behaviorally wayâ hence, detenty reaching and hoping of responsible bahavioral socially.